O uso da língua Sateré-Mawé na Escola Municipal Mércia Cardoso Coimbra: identidade e valorização da cultura indígena na escola urbana - Souza, Samara Santos de (Brasil, 2025)
It is noted that in Brazil there are 10 municipalities with the largest number of indigenous people, Manaus (AM), São Gabriel da Cachoeira (AM), Tabatinga (AM), Salvador (BA), São Paulo de Olivença (AM), Pesqueira ( PE), Autazes (AM), Boa Vista (RR), Tefé (AM) and São Paulo (SP). The municipality of Parintins, na economic hub in the Lower Amazon, also receives indigenous peoples from the Sateré-Mawé and Hixkaryana ethnic groups. This population is made up of children, teenagers and young people who study in urban schools in the municipal and state schools. Considering this context, the present study aims to understand and teach the Sateré-Mawé Language in the initial years of Elementary School at E.M. Mércia Coimbra, describing the strategies/methodologies used by the Mother Tongue teacher to teach the Sateré-Mawé Language to the students in the Initial Years of Elementary School at E.M. Mércia Coimbra, the process of teaching the Sateré-Mawé Language was identified as currently contributing to the strengthening of indigenous identity within urban schools and analyzing the impact of teaching the Sateré-Mawé language and presence of a mother tongue teacher in the educational process of indigenous children in urban schools. The research was carried out in a municipal school that serves approximately 40 indigenous students, and has the support of a mother tongue teacher. The ethnographic research used participant observation, semi-structured interviews and document analysis as data collection techniques. The observations were recorded in the field notebook. By learning about how the teaching of the indigenous language occurs, the experiences, the meeting made it possible to outline strategies to enable intercultural education that strengthens the identity of indigenous children in na urban school.